Increasing maternal age predicts placental protein expression critical for fetal serotonin metabolism: Potential implications for neurodevelopmental research. (December 2022) - Levitan, Robert D.; Sqapi, Maria; Post, Martin; Knight, Julia A.; Lye, Stephen J.; Matthews, Stephen G.
Abstract: High fetal exposure to serotonin and increasing maternal age both contribute to the risk for neurodevelopmental disorders. While identifying covariates for a study of placental protein expression, we found a significant negative correlation between maternal age and the expression of monoamine oxidase A ( MAOA ), and a significant positive correlation between maternal age and the expression of the serotonin transporter SERT. MAOA and SERT play key roles in placental serotonin metabolism relevant to fetal neurodevelopment. These preliminary findings suggest that the effect of increasing maternal age on neurodevelopmental risk may be mediated in part by changes in placental protein expression relevant to fetal serotonin metabolism. Highlights: Increasing maternal age and high serotonin contribute to neurodevelopmental risk. We found maternal age predicted the expression of two placental serotonin proteins. In both cases the findings would increase fetal brain exposure to serotonin. Maternal age may affect neurodevelopment via serotonin placental protein expression.